2021
DOI: 10.3390/cancers13184663
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Endocrine Trans-Differentiation Approach to Pancreatic Ductal Adenocarcinoma Cells with Different EMT Phenotypes Identifies Quasi-Mesenchymal Tumor Cells as Those with Highest Plasticity

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive and therapy-resistant cancer types which is largely due to tumor heterogeneity, cancer cell de-differentiation, and early metastatic spread. The major molecular subtypes of PDAC are designated classical/epithelial (E) and quasi-mesenchymal (QM) subtypes, with the latter having the worst prognosis. Epithelial–mesenchymal transition (EMT) and the reverse process, mesenchymal-epithelial transition (MET), are involved in regulating invasion/meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…We have previously shown that the RAC1 splice isoform, RAC1b, acts as an endogenous inhibitor of RAC1 in the regulation of EMT and cell migration in PDAC-derived cells, consistent with low or absent expression of RAC1b in the QM cell lines PANC-1, MIA PaCa-2, and PaTu 8988s [ 23 , 30 , 32 ]. To study if RAC1b also impacts the deTDtP, we ectopically expressed in a stable or transient fashion an HA-tagged version of RAC1b in PANC-1 or MIA PaCa-2 cells, respectively.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…We have previously shown that the RAC1 splice isoform, RAC1b, acts as an endogenous inhibitor of RAC1 in the regulation of EMT and cell migration in PDAC-derived cells, consistent with low or absent expression of RAC1b in the QM cell lines PANC-1, MIA PaCa-2, and PaTu 8988s [ 23 , 30 , 32 ]. To study if RAC1b also impacts the deTDtP, we ectopically expressed in a stable or transient fashion an HA-tagged version of RAC1b in PANC-1 or MIA PaCa-2 cells, respectively.…”
Section: Resultsmentioning
confidence: 64%
“…The expression and functional activity of the N17 mutant were verified here by immunoprecipitation ( Figure S1, Figure S12, left-hand panel ) and its ability to reduce basal migration of PANC-1 cells ( Figure S2 ) mimicking the loss in migratory activity after siRNA-mediated RAC1 knockdown [ 36 ]. Following application of an FGFb + TF-based protocol [ 14 ] for induction of a β cell transcriptional program—assessed by expression of INS, SLC2A2, and MAFA [ 23 ]—we noted that the induction of these markers was clearly impaired upon dn inhibition of RAC1 activation ( Figure 1 A). Similar results for INS expression were obtained with MIA PaCa-2 cells transiently transfected with an RAC1 N17 -encoding expression vector ( Figure 1 B and Figure S1, middle panel ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations